(untitled) (Revista Educação Especial em Debate, 2021)
Agda Felipe Silva Gonçalves (Ufes) Aline de Menezes Bregonci (Ufes) Andressa Mafezzoni Caetano (Ufes) Anna Maria Lunardi Padilha (Instituto de Pesquisa Heloísa Marinho) Douglas Christian Ferrari de Melo (Ufes) Euluze Rodrigues Costa Junior (Ufes) Fernanda de Araújo Binatti Chiote (Criarte/Ufes) Ivone Martins de Oliveira (Ufes) Isabel MatosNunes (Ufes) Keila Cardoso Teixeira (Ufes) Keli Simões Xavier Silva (Ufes) Marileide Gonçalves França (Ufes) Michell Pedruzzi Mendes Araújo (UFG) Rosana Carla do Nascimento Givigi (UFS) Sonia Lopes Victor (Ufes) Sirleine Brandão de Souza (UFMG) Washington Cesar Shoiti Nozu (UFGD) Vitor Gomes (Ufes)